Dynamic Strain in the Canine Tibia: an in vivo Strain Gauge Analysis - Matushek, K. J.; Sumner-Smith, G.; Schatzker, J.; Hearn, T. C.; Taves, C.; Hoare, I. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
Electrical resistance rosette strain gauges were bonded directly to the surface of the midshaft of the tibia in four dogs. In vivo strain recording were obtained using a telemetric system allowing the dog relatively free movement. During the stance phase of walking, the cranial surface was mainly in tension while the caudal surface was mainly in compression. The pattern of strain recorded is consistent with craniocaudal bending superimposed on external torsion at the stifle.
Keywords: Strain gauge; Tibia; Bone loading